Determinan Ekspor Negara ASEAN-3 ke China Sebelum dan Sesudah ACFTA - Ivana, Aisyah Fayi; Aisyah, Siti (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine whether the exports of 3 ASEAN member countries, namely Indonesia, the Philippines, and Vietnam to China experienced significant changes both before and after the ACFTA (ASEAN – China Free Trade Area) agreement, and whether macroeconomic factors such as population, per capita income, foreign direct investment, exchange rates and inflation rates have different effects on exports to China. The findings in this study indicate that the exchange rate, per capita income and foreign direct investment have a positive and significant effect, while other factors such as population, inflation rates and the implementation of ACFTA have a negative and significant effect on the exports of 3 ASEAN countries to China.